2019
DOI: 10.1016/j.jhydrol.2019.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for estimating unsaturated soil hydraulic conductivities at various bulk densities with the extended Mualem-van Genuchten model

Abstract: The Mualem-van Genuchten model has been widely used for estimating unsaturated soil hydraulic conductivity (Ku) from measured saturated hydraulic conductivity (Ks) and fitted water retention curve (WRC) parameters. Soil bulk density (ρb) variations affect the accuracy of Ku estimates. In this study, we extend the Mualem-van Genuchten model to account for the ρb effect with ρb-related WRC and Ks models. We apply two functions (A and B) that relate the van Genuchten WRC model to ρb and two models (1 and 2) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Since adding compost alters the mean particle density of the material, materials at the same bulk density but with different compost amounts will have differing porosity. We chose to use porosity instead of bulk density for differentiation between compaction levels because changes in porosity are considered one of the main factors altering the soil hydraulic properties with and without the addition of compost (Tian et al, 2018(Tian et al, , 2019. Thus, by holding the porosity constant across compost levels, the direct effect of the compost addition, rather than the effect of change in porosity associated with compost addition, could be compared.…”
Section: Materials Preparationmentioning
confidence: 99%
“…Since adding compost alters the mean particle density of the material, materials at the same bulk density but with different compost amounts will have differing porosity. We chose to use porosity instead of bulk density for differentiation between compaction levels because changes in porosity are considered one of the main factors altering the soil hydraulic properties with and without the addition of compost (Tian et al, 2018(Tian et al, , 2019. Thus, by holding the porosity constant across compost levels, the direct effect of the compost addition, rather than the effect of change in porosity associated with compost addition, could be compared.…”
Section: Materials Preparationmentioning
confidence: 99%
“…The measurements were performed on unsaturated soil in situ [62]. Although the values found are below expectations in saturated soil experiments, G also had the highes conductivity (35.8 mm h −1 ) and was significantly higher than all other areas.…”
Section: Hydraulic Conductivity and Infiltration Velocitymentioning
confidence: 71%
“…The unsaturated hydraulic conductivity (K u ) was then calculated from K s and the WRC parameters. Results by Tian et al (2019) showed that Model 2 produced more accurate estimates of K u than Model 1, with Model 2 providing a better description of the WRC near saturation. Thus, we used an equation similar to Model 2 of Tian et al ( 2019) to determine K s and K u , and to be able to account for the effects of compaction on the hydraulic conductivity and water infiltration:…”
Section: Effect Of Compaction On the Hydraulic Conductivitymentioning
confidence: 97%
“…hydraulic conductivity. Tian et al (2019) developed two models for estimating the saturated hydraulic conductivity (K s ) at various soil bulk densities. Their first model (Model 1) was based on the Carman-Kozeny equation (Kruczek, 2016), whereas the second model (Model 2) used the Mualem and Assouline (1989) semitheoretical model and the VG water retention function (van Genuchten, 1980).…”
Section: Effect Of Compaction On the Hydraulic Conductivitymentioning
confidence: 99%